Pengaruh Latihan Kekuatan Jari-Jari Tangan Terhadap Peningkatan Kemampuan Passing Atas Dalam Permainan Bola Voli Pada Siswa Putra Kelas VIII SMP Negeri 1 Indralaya - Satria, M Haris (UIR Press, 2019)
This research aimed to determine the effect of fingers strength training toward fingers overhead passing skill. This research was experimental design. The population in this research was VIII grade male students and the sample were 60 students which selected by random sampling technique (ordinal pairing). This research used one experimental group and one control group. The experimental group was taught by using fingers overhead passing training but control group was without it. The data was conveyed through pre-test and post-test. Instrument of this research was overhead passing test. And then, the data was analyzed by using t-test. Based on the research result, t observed (1.85) was higher than t table (1.673). It can be concluded that H0 was rejected and Ha was accepted. It means that there was significant effect of using fingers strength training toward students’ fingers overhead passing of VIII grade students of SMPN 1 Indralaya.